Symptoms, unmet needs, psychological well‐being and health status in survivors of prostate cancer: implications for redesigning follow‐up. (23rd May 2015) - Watson, Eila; Shinkins, Bethany; Frith, Emma; Neal, David; Hamdy, Freddie; Walter, Fiona; Weller, David; Wilkinson, Clare; Faithfull, Sara; Wolstenholme, Jane; Sooriakumaran, Prasanna; Kastner, Christof; et al.
Abstract : Objective: To explore ongoing symptoms, unmet needs, psychological wellbeing, self‐efficacy and overall health status in survivors of prostate cancer. Patients and Methods: An invitation to participate in a postal questionnaire survey was sent to 546 men, diagnosed with prostate cancer 9–24 months previously at two UK cancer centres. The study group comprised men who had been subject to a range of treatments: surgery, radiotherapy, hormone therapy and active surveillance. The questionnaire included measures of prostate‐related quality of life (Expanded Prostate cancer Index Composite 26‐item version, EPIC‐26); unmet needs (Supportive Care Needs Survey 34‐item version, SCNS‐SF34); anxiety and depression (Hospital Anxiety and Depression Scale, HADS), self‐efficacy (modified Self‐efficacy Scale), health status (EuroQol 5D, EQ‐5D) and satisfaction with care (questions developed for this study). A single reminder was sent to non‐responders after 3 weeks. Data were analysed by age, co‐morbidities, and treatment group. Results: In all, 316 men completed questionnaires (64.1% response rate). Overall satisfaction with follow‐up care was high, but was lower for psychosocial than physical aspects of care. Urinary, bowel, and sexual functioning was reported as a moderate/big problem in the last month for 15.2% ( n = 48), 5.1% ( n = 16), and 36.5% ( n  = 105) men, respectively. The most commonly reported moderate/high unmet needs related to changes in sexual feelings/relationships, managing fear of recurrence/uncertainty, and concerns about the worries of significant others. It was found that 17% of men (51/307) reported potentially moderate‐to‐severe levels of anxiety and 10.2% (32/308) reported moderate‐to‐severe levels of depression. The presence of problematic side‐effects was associated with higher psychological morbidity, poorer self‐efficacy, greater unmet needs, and poorer overall health status. Conclusion: While some men report relatively few problems after prostate cancer treatment, this study highlights important physical and psycho‐social issues for a significant minority of survivors of prostate cancer. Strategies for identifying those men with on‐going problems, alongside new interventions and models of care, tailored to individual needs, are needed to improve quality of life.